Analysis of convergence trends and driving factors of environmental efficiency of pig farming in China - Jingjing Wang; Chang'e Zhao; Silin Chen (Frontiers in Sustainable Food Systems, 2025)
IntroductionThis study aims to clarify the development characteristics, differences, and convergence trends of environmental efficiency in China’s pig industry, which helps promote the sustainable development of the pig industry.MethodsBased on the data of 30 provinces (municipalities and autonomous regions) in China from 2008 to 2020, this article used the super-SBM model, log (t) test, and ordered probit model to estimate the environmental efficiency and convergence trend of pig farming in China and analyzed the driving factors affecting the convergence trend.ResultsThe results showed that: (1) In recent years, the environmental efficiency of pig farming in China did not reach the optimal state, and the environmental efficiency of the potential growth region was the highest, reaching 71.6%. Scale efficiency is still the key to improving the environmental efficiency of pig farming, and in the future, it is necessary to focus on improving pure technical efficiency. (2) The environmental efficiency of pig farming across China’s 30 provinces (including municipalities and autonomous regions) converges to four clubs. Most provinces within constrained development regions and potential growth regions converge to the high-level club, while the disparities in environmental efficiency of pig farming are most pronounced in key development regions. (3) The research results of driving factors show that scale level exhibits a “U-shaped” effect on the convergence of environmental efficiency in pig farming toward high-level clubs in China, and most provinces have surpassed the inflection point. The scale level of pig farming should be appropriately improved. In addition, improving the quality of the labor force can help the environmental efficiency of pig farming converge to a high-level club.DiscussionWe propose suggestions aimed at enhancing the efficiency of pig farming, promoting the scale processes of pig farming, and strengthening regional cooperation.